Natura 2000 Within Discursive Space: The case of the Ria de Aveiro - Sumares, D.
The Ria de Aveiro, a Portuguese estuary protected under Natura 2000, has suffered strong development pressures in recent decades which, in combination with the decline of traditional activities, have caused severe environmental problems. To produce a description of the context's discursive dimension and identify obstacles for collaborative and coherent management of this complex socio-ecological system, we have analysed the consultations related to the environmental assessment of five development projects and a programme for ‘integrated redevelopment and enhancement operations’ in priority coastal areas. The exact meaning of sustainability regarding the estuary is far from consensual among the different participants, and is often in conflict with the vision behind the planned interventions. In this paper, we identify and discuss key themes in local discourses that dialectically interrelate in ways that need to be considered by this territory's environmental governance and argue for the importance of discursive explorations on a case-by-case basis.